Commercialization of green technology projects in Kazakhstan: key factors and barriers (Вестник КазНУ. Серия Экономическая, 2017)
Green technologies are essential tools to ensure sustainable developmentof the economy. The transition to a green economy requires changesin existing governance approaches, institutions, and markets. One of theimportant indicators is a successful implementation of research results ingreen technologies. In this regard, the author analyzed green technologyprojects in Kazakhstan in terms of commercialization. Research objectivesare to patent analysis of projects and to identify key factors and barriersthat affect the successful commercialization of technologies based on the respondents’opinions. Interviews with representatives of 14 green technologyprojects and 9 experts were conducted and analyzed. In the result of total23 interviews factors and barriers affecting the commercialization of greentechnologies in Kazakhstan were identified. The overwhelming majority ofexperts emphasized the importance of financial, infrastructural, technologicaland personnel factors. It is necessary to take into account all mentionedfactors and develop complex measures to overcome barriers. That would bebasis for successful of transition from “brown” to green economy.